Expressive Appropriateness in contemporary architectural production - Suha Hassan AL-Dahwi; Binar Abdul-Hameed Al jaf (Iraqi Journal of Architecture and Planning, 2018)
The concept of Appropriateness has emerged by thousands of years, since the architect Vitruvius, as one of the most important theoretical aspects that achieve integrated architecture. It has evolved over the years in the postmodern architecture to the importance of the recipient and his reading of the architectural text. The concept varied and numerous  such as ( functional, structural, expressive , environmental, social, and economic) Appropriateness . The research emerged many of the architectural and non architectural studies related to the concept of Appropriateness, where achieved to the importance of the expressive side and expressive Appropriateness. The research identified problem as "Lack of a comprehensive & objective perception about the  expressive Appropriateness in contemporary architectural production and the relationship between the designer intentions and the mechanisms of expressive Appropriateness on one hand and what actually achieved in production on the other ". The goal of this research is to "form an objective and comprehensive framework for expressive appropriateness properties in the contemporary architectural production and explore the relationship between the designer intentions and the mechanisms on one hand and what actually done in the production according to the opinion of the recipient" . The research built a framework contained a primary and secondary items , then elected goals and mechanisms of expressive Appropriateness and applied them on an elected group of contemporary architectural projects after an analytical study of these projects. The  conclusions concerning the multiple mechanisms achieved and concatenated as they arise (encoding and metaphor and similarity), and the variation of expressive Appropriateness achievement is due to the diversity of goals and mechanisms adopted.